PENGARUH KOMPETENSI, INDEPENDENSI, ETIKA, PENGALAMAN AUDITOR, DAN TEKANAN ANGGARAN WAKTU TERHADAP KUALITAS AUDIT - Stella Angelina (Jurnal Bina Akuntansi, 2017)
The objective of this research is to examine the influence of auditor's competency, independency, ethic, experience, and time budget pressure toward audit quality. The object of this research is public accountants (external auditor) that working at Public Accounting Firm in Jakarta and Tangerang. This research was conducted using a survey method. Data were collected using questionnaires. From 180 questionnaires distributed, 119 questionnaires were returned, and 28 questionnaires were not meet the criteria, so that only 91 questionnaire could be process. Data analysis conducted with multiple linear regression model. The result of this study were competency, independency, ethic, experience, and time budget pressure have significant influence to audit quality simultaneously. Competency, independency, experience, and time budget pressure have significant influence to audit quality partially. But, ethic not have significant influence to audit quality partially.